Insufficient Efficacy of Corpus Callosotomy for Epileptic Spasms With Biphasic Muscular Contractions - Kanai, Sotaro; Okanishi, Tohru; Nishimura, Mitsuyo; Oguri, Masayoshi; Enoki, Hideo; Maegaki, Yoshihiro; Fujimoto, Ayataka (Frontiers in Neurology, 2020)
Corpus callosotomy (CC) is the surgical strategy for drug-resistant epileptic seizures including epileptic spasms (ES). In this study we report a subtype of ES which is accompanied by two consecutive muscular contractions. This subtype has not been previously classified and may emerge via a complex epileptic network. We named these seizures “epileptic spasms with biphasic muscular contractions (ES-BMC)” and analyzed the association between them and CC outcomes. We enrolled 17 patients with ES who underwent CC before 20 years of age, and analyzed the records of long-term video-electroencephalogram (EEG) recordings. The outcomes of CC were ES-free (Engel's classification I) in 7 and residual ES (II to IV) in 10 patients. We statistically analyzed the associations between the presence of preoperative ES-BMC and the outcomes. Ages at CC ranged from 17 to 237 months. We analyzed 4–44 ictal EEGs for each patient. Five patients presented with ES-BMC with 6–40% of their whole ES on the presurgical video-EEG recordings, and all of them exhibited residual ES outcomes following CC. A Fisher's exact test revealed a significant positive correlation between the presence of preoperative ES-BMC and persistence of ES following CC (p = 0.044, odds ratio = 15.0, risk ratio = 2.0). The presence of ES-BMC may be useful in the presurgical prediction of CC outcomes in patients with ES.